2016
DOI: 10.5348/d05-2016-20-oa-16
|View full text |Cite
|
Sign up to set email alerts
|

The glittre-ADL test can be used to assess the functional performance in patients with leprosy: A controlled transversal study

Abstract: Aims: The purpose of this study was to assess functional capacity in leprosy patients by using the Glittre-ADL test, comparing it with the performance of healthy subjects, and correlating with the Screening of Activity Limitation and Safety Awareness (SALSA) scale and quality of life (QoL). Methods: A controlled transversal study was conducted with 27 participants, 16 patients with leprosy (Leprosy Group, LG) and 11 healthy participants (Control Group, CG). Eligible participants performed the Glittre ADL-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Leprosy patients indicated worse QoL scores when compared to the general population (15,22,24,33,37,40,66) .…”
Section: Main Findingsmentioning
confidence: 88%
See 3 more Smart Citations
“…Leprosy patients indicated worse QoL scores when compared to the general population (15,22,24,33,37,40,66) .…”
Section: Main Findingsmentioning
confidence: 88%
“…The studies included in this review showed that leprosy individuals had significantly lower QoL when compared to populations with other dermatoses (35,71) and the general population (15,22,24,33,37,40,66) , which is corroborated by other studies that indicate that factors such as delayed diagnosis (2,8,43,74,76,(78)(79) , the presence of leprosy reactions (2,8,16,(61)(62)72) , disability (5,8,39,72) , neuropathic pain (7,(17)(18)63,86) , and stigma (2,41,54) are often associated with greater losses in QoL.…”
Section: Main Findingsmentioning
confidence: 97%
See 2 more Smart Citations